Analisis Persimpangan Hukum Positif Dan Perilaku Masyarakat Desa Karangharjo, Silo, Jember Dikaji Melalui Pendekatan Sosiologi Hukum - Mohammad Misbaqul Arfah; Ichah Yunia Rahmawati; Dhaifina Dewita Ayu; Siti Faizeh; Fauzi Rohman; Tasya Defana Belinda; Iyaksa Tirta Amukti (Public Service and Governance Journal, 2024)
This research discusses the phenomenon of the people of Karangharjo Village, Silo District, Jember Regency who tend to behave deviantly from positive Indonesian law, more specifically related to the problem of early marriage, high rates of divorce, domestic violence and high cases of stunting that occur in children which is normalized by local community. In 2022, there will be 50,673 applications for marriage dispensation, 516,344 divorce cases, where 80% of these divorce cases are experienced by couples who have been together for less than 5 years. This research was studied using a qualitative descriptive approach and legal sociology, and the analysis of this research data was empirical. To find out about the behavior of the people of Karangharjo Village, Silo District, Jember Regency who deviate from positive law in Indonesia. Data collection techniques in this research were carried out using interviews, observations and document review. There were 10 informants interviewed. This village was used as an object because it was considered to be one of the sub-districts that applied for the highest marriage dispensation in Jember Regency. Researchers succeeded in answering social impacts, including the factors that cause early marriage due to people's concerns about deviations from the nature of religion if their children are not married immediately, apart from that, the perspective emerged that if children aged 20 years have not been married, this is considered a disgrace for the family in Karangharjo Village. The causality of this deviation results in high stunting rates due to mental, economic and psychological unpreparedness in establishing a harmonious household. Community behavior tends to deviate, where traditions and cultural customs are upheld more highly than positive law itself. Therefore, an approach is needed to understand people's behavior so that they comply with positive law without exception, namely by using a legal sociology of law.